A Review of Self-Management Interventions for People With Dementia and Mild Cognitive Impairment. (November 2016) - Quinn, Catherine; Toms, Gill; Anderson, Daniel; Clare, Linda
Self-management offers a way of helping people with dementia or mild cognitive impairment (MCI) to play an active role in managing their condition. Barlow, Wright, Sheasby, Turner, and Hainsworth have defined self-management as the "individual's ability to manage the symptoms, treatment, physical and psychosocial consequences and life style changes inherent in living with a chronic condition." Although commonly used in other chronic health conditions, there has been relatively little exploration of the role of self-management in dementia or MCI. This review aimed to identify group-based psychosocial interventions for people with dementia or MCI that incorporate significant elements of self-management. Fifteen interventions were included in the review: 12 for people with dementia and 3 for participants with MCI. In both the dementia and MCI interventions, the most commonly included self-management components were information, communication, and social support, and skills training. The review findings indicate that components of self-management have been incorporated into group-based interventions for people with dementia and MCI. Further studies are needed to address the methodological limitations of the included studies and to determine the effectiveness of self-management interventions with these populations.